Peningkatan Hasil Belajar Materi Teks Deskripsi Menggunakan Model Pembelajaran Kooperatif Tipe "Make A Match" - Citra Gloria Tappi; Sakinah Fitri (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2026)
This research aims to explore the application of the "Make A Match" cooperative learning model in improving students' learning outcomes on descriptive text material. This model allows students to actively collaborate, encouraging conceptual understanding through matching information. Using a qualitative approach with a case study design, the research was conducted in Class VII 9 at SMP Negeri 24 Makassar, involving 30 students. Data were collected through observation, interviews, and documentation. The results showed a significant increase in the students' average score from 65 to 85 after the implementation of the "Make A Match" model. In addition, this model also enhanced students' collaborative skills, critical thinking, and learning motivation. The application of this method not only strengthened academic understanding but also created an interactive and enjoyable learning atmosphere, as well as developed students' social skills.